Study on stress corrosion behavior and failure mechanism of galvanized bolts in complex coal mine environments - Zhe He; Nong Zhang; Zhengzheng Xie; Chao Ma; Changliang Han; Fan Zhang; Huiqing Wang; Saad S. Alarifi (Journal of Materials Research and Technology)
The premature failure of bolts caused by stress corrosion cracking (SCC) is a common issue in the global mining industry. Studies have shown that hot-dip galvanizing is an effective solution, but the first widespread application of galvanized bolts in Xin’Shang’Hai No. 1 coal mine, China, experienced extensive failures. To thoroughly investigate the fracture failure mechanism, this paper employed a comprehensive approach that included macro mechanical property testing, corrosion experiments, and micro-scale characterization. The findings indicate that significant stress concentration occurred on the surface threads of the bolts under high mine pressure, serving as the primary inducer of SCC in the bolts. Under long-term stress corrosion conditions, the peak strength of high-strength coated bolts, hot-dip galvanized bolts, and ordinary bolts decreased by 3.73%, 20.54%, and 11.60% respectively. Among them, the coated bolts largely maintained their original mechanical properties and had the best anti-corrosion capability. The performance of galvanized bolts deteriorated more than ordinary ones, indicating that they could not suppress the SCC of the bolts and even exacerbated the SCC of the bolt body after the galvanized layer cracked. Hydrogen content analysis showed that after service in the mine, the hydrogen content in the body of the galvanized bolts increased by 304.48%, significantly raising the risk of hydrogen induced cracking (HIC). Additionally, HIC-sensitive structures (tempered martensite) and typical features of HIC (white spots) were found in the galvanized bolts, providing strong evidence of HIC occurrence during their service in the mine. In short, the instantaneous fracture of galvanized bolts was mainly caused by the interaction of stress concentration cracking due to the geometry of the bolts and HIC under stress corrosion failure. Thus, in deep underground engineering, it is not recommended to promote the use of galvanized anti-corrosion processes and Class A shaped bolts, especially in environments with high stress and high mineralization. Instead, high-strength coated bolts are advised to replace galvanized ones to enhance the reliability and safety of bolt support.